Concentration of indoor air chemical parameters at different ship conditions and engine sequences - Nur Sarah Fatihah, Tamsi; Maryam, Zahaba; Amirul Faiz, Kamaruddin; M. S.Mohammad, Naufal; Norhidayah, Abdull; Arman, Ariffin (Akademi Sains Malaysia, 2023)
Good indoor air quality (IAQ) is crucial for navy crew due to longer periods onboard, especially during pandemic. Increased frequency of the ship's operations is required to prevent trespassing and illegal border crossings. This study aims to determine and compare the indoor air chemical parameters; carbon dioxide (CO₂), carbon monoxide (CO), and total volatile organic compounds (TVOC) at different ship conditions (alongside and sailing) and engine sequences (idling, cruising, full ahead and slowing down). The parameters were measured in four compartments, following the Industry Code of Practice on Indoor Air Quality 2010 (ICOP IAQ 2010). At different ship conditions, there were significant differences of indoor air chemical parameters in the common room, electrical room, and accommodation area 2. However, no trend of higher or lower concentrations was observed between the conditions due to ship operation, human activities, and occupancy. The engine sequences affect the indoor air chemical parameters, where the CO concentrations were recorded higher in all compartments, especially when the engine was running at 1000 rpm. In conclusion, the navy crew could be exposed to unacceptable IAQ conditions regardless of ship conditions and engine sequences. It is good to highlight that good ventilation is crucial to dilute the air pollutants onboard.